The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.02.27.22271548
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multicenter international assessment of a SARS-CoV-2 RT-LAMP test for point of care clinical application

Abstract: Continued waves, new variants, and limited vaccine deployment mean that SARS-CoV-2 tests remain vital to constrain the COVID-19 pandemic. Affordable, point-of-care (PoC) tests allow rapid screening in non-medical settings. Reverse-transcription loop-mediated isothermal amplification (RT-LAMP) is an appealing approach. A crucial step is to optimize testing in low/medium resource settings. Here, we optimized RT-LAMP for SARS-CoV-2 and human β actin, and tested clinical samples in multiple countries. TTTT linker … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…The effect of guanidine hydrochloride (GuHCl) on the performance of E-ID1 primer set in both colorimetric and fluorometric RT-LAMP reactions was tested since it was reported to enhance the detection speed and efficiency (Dudley et al, 2020, Lu et al, 2022, Zhang, 2020b). Figure 3 (a) shows two sets of colorimetric RT-LAMP with and without the addition of GuHCl (40 mM) on positive clinical specimens, in addition to PC and NTC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of guanidine hydrochloride (GuHCl) on the performance of E-ID1 primer set in both colorimetric and fluorometric RT-LAMP reactions was tested since it was reported to enhance the detection speed and efficiency (Dudley et al, 2020, Lu et al, 2022, Zhang, 2020b). Figure 3 (a) shows two sets of colorimetric RT-LAMP with and without the addition of GuHCl (40 mM) on positive clinical specimens, in addition to PC and NTC.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement was evident with final concentrations between 40-60 mM in a 25 µL reaction volume, with 40 mM being the optimum recommended concentration <https://international.neb.com>\(Zhang et al, 2020b). Most studies reported this enhancement from GuHCl on RNA-extracted clinical samples but not in direct ones (Dudley et al, 2020, Lu et al, 2022). Based on that, we used 40 mM GuHCl in the colorimetric and fluorometric RT-…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…(20,27,3844). These publications describe many different primer sets and use patient samples without purification (“direct assays”) (some are summarized here: (42)) or with prior purification of RNA, many with optimized procedures where compelling data could be obtained that suggest suitable sensitivity of RT-LAMP for detection of infections in asymptomatic and symptomatic subjects. Yet, intrinsic limitations of simple RT-LAMP assays using colorimetric readouts without sequence-specific probes such as molecular beacons, complicate its practical implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of the pandemic, a large number of publications emerged describing the use and validation of RT-LAMP assays for SARS-CoV-2 diagnostics, i.e. (20,27,(38)(39)(40)(41)(42)(43)(44). These publications describe many different primer sets and use patient samples without purification ("direct assays") (some are summarized here: (42)) or with prior purification of RNA, many with optimized procedures where compelling data could be obtained that suggest suitable sensitivity of RT-LAMP for detection of infections in asymptomatic and symptomatic subjects.…”
Section: Implementation Of a Large-scale Rt-lamp-based Sars-cov-2 Tes...mentioning
confidence: 99%